The mental health in the city of Maranguape: epidemiological aspects of the population assisted in the PSF - Araújo, Michell Ângelo Marques; Silveira, Lia Carneiro (Rev Rene, 2006)
Aiming at identifying epidemiologic aspects and its relationships with the mental health-illness process in the city of Maranguape,we developed a quantitative study, through a questionnaire that approaches aspects concerning the social reproduction and the empowerment/consuming aspects of social groups. The research was made with 106 families which are assisted in the Health Family Program. We noticed that the families which were studied have been facing serious social difficulties such as: familiar low income, harmful living conditions, and insufficient amount of food, among others. Moreover, we perceive the high use of psychotropic and the presence of mental disorders like mental deficiency, epilepsy and chemical dependence. We conclude, therefore, that some efforts are made necessary to improve the population quality of life with the development of mental health actions in several levels of complexity which involve not only the managers and health professionals but the society in general.